Which parametric model for conditional skewness? - Bruno Feunou; Mohammad R. Jahan-Parvar; Roméo Tédongap (Bank of Canada, 2013)
This paper addresses an existing gap in the developing literature on conditional skewness. We develop a simple procedure to evaluate parametric conditional skewness models. This procedure is based on regressing the realized skewness measures on model-implied conditional skewness values. We find that an asymmetric GARCH-type specification on shape parameters with a skewed generalized error distribution provides the best in-sample fit for the data, as well as reasonable predictions of the realized skewness measure. Our empirical findings imply significant asymmetry with respect to positive and negative news in both conditional asymmetry and kurtosis processes.
Keywords: C22; C51; G12; G15; 330; Econometric and statistical methods